Neural Mechanisms Underlying Repetitive Behaviors in Rodent Models of Autism Spectrum Disorders - Gandhi, Tanya; Lee, Charles C. (Frontiers in Cellular Neuroscience, 2021)
Autism spectrum disorder (ASD) is comprised of several conditions characterized by alterations in social interaction, communication and repetitive behaviors. Genetic and environmental factors contribute to the heterogeneous development of ASD behaviors. Several rodent models display ASD-like phenotypes, including repetitive behaviors. In this review, we discuss the potential neural mechanisms involved in repetitive behaviors in rodent models of ASD and related neuropsychiatric disorders. We review signaling pathways, neural circuits and anatomical alterations in rodent models that display robust stereotypic behaviors. Understanding the mechanisms and circuit alterations underlying repetitive behaviors in rodent models of ASD will inform translational research and provide useful insight into therapeutic strategies for the treatment of repetitive behaviors in ASD and other neuropsychiatric disorders.